Simvastatin activates single skeletal RyR1 channels but exerts more complex regulation of the cardiac RyR2 isoform - Venturi, E; Lindsay, C; Lotteau, S; Yang, Z; Steer, E; Witschas, K; Wilson, A; Wickens, J; Russell, A; Steele, D; Calaghan, S; Sitsapesan, R (Wiley, 2017)
Statins are amongst the most widely prescribed drugs for those at risk of cardiovascular disease, lowering cholesterol levels by inhibiting 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase. Although effective in prevention of cardiovascular disease, statin use is associated with muscle weakness, myopathies and, in rare cases, fatal rhabdomyolysis. As simvastatin, a commonly prescribed statin, can promote Ca2+ release from sarcoplasmic reticulum (SR) vesicles, we investigated if simvastatin could directly activate skeletal (RyR1) and cardiac (RyR2) ryanodine receptors.RyR1 and RyR2 single-channel behaviour was investigated after incorporation of sheep cardiac or mouse skeletal SR into planar phospholipid bilayers under voltage-clamp conditions. LC-MS was used to monitor the kinetics of interconversion of simvastatin between hydroxy-acid and lactone forms during these experiments. Cardiac and skeletal myocytes were permeabilised to examine simvastatin modulation of SR Ca2+ release.Hydroxy acid simvastatin (active at HMG-CoA reductase) significantly and reversibly increased RyR1 open probability (Po) and shifted the distribution of Ca2+ spark frequency towards higher values in skeletal fibres. In contrast, simvastatin reduced RyR2 Po and shifted the distribution of spark frequency towards lower values in ventricular cardiomyocytes. The lactone pro-drug form of simvastatin (inactive at HMG-CoA reductase) was also an effective activator of RyR1, suggesting that the HMG-CoA inhibitor pharmacophore was not responsible for RyR1 activation.Our results indicate that simvastatin interacts with RyR1 to increase SR Ca2+ release and thus may contribute to its reported adverse effects on skeletal muscle. The ability of low concentrations of simvastatin to reduce RyR2 Po may also protect against Ca2+ -dependent arrhythmias and sudden cardiac death.